(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف هذا البحث التعرّفُ على جودة هياكل الرقابة الداخلية في الشركات الصناعية الأردنية ومدى انسجامها مع هيكل الرقابة وفقا لإطار لجنة رعاية المؤسسات (COSO). ولتحقيق أهداف هذا البحث طوّرت استبانة شملت اثنتين وثلاثين فقرة وزعت على الشركات الصناعية الأردنية المدرجة في بورصة عمان لعام 2007، وقد استرد منها 48 استبانةً خُضع منها للتحليل الإحصائي 42 استبانة بما نسبته 62.7% من مجتمع البحث (67 شركة). ولاستخلاص النتائج، ولاختبار الفروض استخدم في البحث اختبار t-test للعينة الواحدة وتحليل التباين الأحادي One-Way ANOVA. وقد أظهر البحث وجود هياكل رقابة داخلية جيدة في الشركات الصناعية الأردنية. كما وجد أيضا بعض نواحي الضعف في المجالات التالية: كفاية الأفراد، وجود أنظمة لوصف الأعمال وبيان المسؤوليات، إنتاج معلومات لانجاز الوظائف التخطيطية والرقابية، قدرة أنظمة المعلومات على توفير المعلومات، وتوفير تقارير أداء إدارية، التقييم المستمر لإجراءات الرقابة. The objective of this research is to recognize the quality of the structure of internal control in Jordanian industrial companies and whether they are consistent with the structure initiated by Committee of Sponsoring Organizations (COSO) .In order to achieve this objective a questionnaire was developed and distributed to entire target population of Jordanian Industrial companies, which are listed on Amman Stock Exchange. Forty-eighty of the questionnaires were returned, of which forty-two were found usable, forming a ratio of (62.7%) of the target population. To test the hypotheses, One Sample t-test and One-Way ANOVA were used. The results of this research show that Jordanian industrial companies have, in general, good structure of internal control. The results also show some deficiencies in the following areas: lack of skilled staff, existence of systems to describe functions and authorities, producing of information for planning and control, ability of information systems to provide information, providing of management performance reports, and periodical evaluations of control procedures.